The Influence of WhatsApp Usage to Learning Motivation on Indonesian Languange Subjects - Risna Arianti; Akmal Hamsa; Idawati Idawati (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract. At this time, online learning is increasingly being used in schools. One of the most widely used online learning applications is WhatsApp. Therefore, this research is important to do. This study aims to: (1) describe the use of WhatsApp for Class VII students of SMP Negeri 24 Makassar in Indonesian subjects; (2) describe the motivation to learn Indonesian for Class VII students of SMP Negeri 24 Makassar; and (3) proving the effect of using WhatsApp on the motivation to learn Indonesian in Class VII SMP Negeri 24 Makassar. This research uses quantitative research with ex post facto method. The population in this study were all students of Class VII SMP Negeri 24 Makassar in the academic year 2020/2021, with a total of 360 people. Sampling in this study used a stratified random sampling technique by determining the number of samples using the Slovin formula so that there is 78 samples for research. The instrument in this study was a closed questionnaire using a Likert scale. Data analysis in this study used the SPSS application version 26. The results showed that: (1) the level of students WhatsApp use is in the high category; (2) the level of students motivation to learn Indonesian is in the high category; and (3) the result of regression test showed that the use of WhatsApp had a positive and significant effect on students motivation to learn Indonesian by 20,9%> The regression coefficient test value is 0,572. This value shows that for every 1% addition to the level of WhatsApp usage, the value of students Indonesian learning motivation increases by 0,572. The regression coefficient is positive so that the direction of the influence of the variable X on Y is positive.Keywords: Influence, WhatsApp, Motivation